Energi Kinetik Alat Kebugaran Lat Pull Down untuk Lampu LED dan Pemandu - Deddy Susilo; F. Dalu Setiaji; Martino Suherman (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2015)
This research builds a fitness equipment Lat Pull Down which is modified to produce alternative energy. This tool works by pulling a lever connected to a gearbox. Rotor and generator are connected to the gearbox and will rotate with angular velocity at about 22 rad/s, thus, can generate electromotive force of about 202 V. This AC voltage will be converted by a full wave rectifier using Schottky diodes into 19,8 VDC. An electronic switch, then, will automatically connect the DC voltage, which is still fluctuative, to either an LM2577 or LM2576 chip that will increase or decrease the voltage, respectively, into a stable voltage of 13,8 V. The energy will be stored in the 12 V accumulator and can be used as an energy source for the 2,5 W LED and microcontroller-based guidance system. This system can generate energy up to 2,367 Wh each day.